2018
DOI: 10.3389/fbioe.2018.00173
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiating Astrocytes Into Neurons Using ASCL1 Functionalized With a Novel Intracellular Protein Delivery Technology

Abstract: Cellular transdifferentiation changes mature cells from one phenotype into another by altering their gene expression patterns. Manipulating expression of transcription factors, proteins that bind to DNA promoter regions, regulates the levels of key developmental genes. Viral delivery of transcription factors can efficiently reprogram somatic cells, but this method possesses undesirable side effects, including mutations leading to oncogenesis. Using protein transduction domains (PTDs) fused to transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Spontaneous and evoked synaptic responses in these glia-derived NeuroD1-converted neurons suggest that the iN integrated into local neural circuits (Guo et al, 2014). Increased plasticity in reactive astrocytes resulted in higher conversion rates when compared against non-reactive astrocytes (Brulet et al, 2017;Robinson et al, 2018). In a stroke model, in vivo direct reprogramming of astrocytes to iN following stroke resulted in improvements in motor function as soon as 3 weeks after the reprogramming process, with sustained long-term functional recovery (Livingston et al, 2020).…”
Section: Astrocytesmentioning
confidence: 99%
“…Spontaneous and evoked synaptic responses in these glia-derived NeuroD1-converted neurons suggest that the iN integrated into local neural circuits (Guo et al, 2014). Increased plasticity in reactive astrocytes resulted in higher conversion rates when compared against non-reactive astrocytes (Brulet et al, 2017;Robinson et al, 2018). In a stroke model, in vivo direct reprogramming of astrocytes to iN following stroke resulted in improvements in motor function as soon as 3 weeks after the reprogramming process, with sustained long-term functional recovery (Livingston et al, 2020).…”
Section: Astrocytesmentioning
confidence: 99%
“…However, due to their low efficiency, transgene silencing, inflammation and poor nuclear uptake, are less commonly used in transdifferentiation studies [ 45 ]. Lately, the use of neural exosomes [ 46 ] and the protein transduction domains (PTDs) fused to TFs allow the direct delivery of exogenous TFs avoiding the problems associated with DNA integration into the host genome [ 47 ] opening up new strategies for possible clinical applications.…”
Section: Commentarymentioning
confidence: 99%
“…The inability to produce the neuronal subtypes which are lost in neurodegenerative disorders like Parkinson’s disease, Alzheimer’s disease, Amyotrophic Lateral Sclerosis, Huntingdon’s disease represents a major limitation in current small molecules transdifferentiation field. However, it was showed that a single TF such as ASCL1, using a novel protein intracellular delivery technology, in combination with the small molecules LDN193189, SB431542, DAPT and valproic acid can rapidly reprogram astrocytes into mature GABAergic and glutamatergic interneurons with high efficiency [ 47 ]. Moreover, Chabrat et al developed a novel in vitro model of dopaminergic-like neurons derived from human nasal olfactory stem cells through a six step transdifferentiation protocol based on a specific combination of signaling pathway modulators [ 60 ].…”
Section: Commentarymentioning
confidence: 99%
“…Further work showed that the proneural factor ASCL1 alone was able to guide the conversion of human fibroblasts into a mix of glutamatergic and GABAergic neurons [ 77 ]. Interestingly, ASCL1 promoted reprogramming of astrocytes to mainly GABAergic neurons [ 78 ]. This highlighted that the effect of transcription factor to reprogram cell fate is partly dependent on the starting cell type.…”
Section: Direct Reprogramming To Generate Neurons Using Transcriptmentioning
confidence: 99%